2005
DOI: 10.1097/01.rlu.0000159680.66566.b7
|View full text |Cite
|
Sign up to set email alerts
|

FDG Uptake in a Catheter-Related Thrombus Simulating Relapse of Lymphoma

Abstract: FDG-PET imaging was performed because of suspected recurrence of lymphoma of the chest. There was an area of increased activity posterior to the left sternoclavicular joint, suspected of being a relapse. Workup showed a thrombus at the tip of a central venous line corresponding to the FDG uptake. This is explained by the inflammatory process involving and surrounding chronic thrombus. Focal activity in relation to the tip of a venous catheter is very likely to have a benign etiology. It is important to recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 8 publications
0
47
0
Order By: Relevance
“…Miceli et al [12] suggested that 18 F-FDG accumulated in all cases of thrombophlebitis but not in deep venous thrombosis. In earlier literature, it has been reported that 18 F-FDG may accumulate in neutrophils and macrophages in the area of infl ammation and may not accumulate in non-infl ammatory clot and organizing clot [8,10]. We consider that it may be possible to distinguish between tumor thrombus and venous thrombus.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Miceli et al [12] suggested that 18 F-FDG accumulated in all cases of thrombophlebitis but not in deep venous thrombosis. In earlier literature, it has been reported that 18 F-FDG may accumulate in neutrophils and macrophages in the area of infl ammation and may not accumulate in non-infl ammatory clot and organizing clot [8,10]. We consider that it may be possible to distinguish between tumor thrombus and venous thrombus.…”
mentioning
confidence: 78%
“…We consider that it may be possible to distinguish between tumor thrombus and venous thrombus. 18 F-FDG uptake has been reported to be seen in catheter-related thrombus [10,13]. However, this phenomenon occurred because of infl ammatory change of the venous wall stimulated by the catheter.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…It is known that tumour thrombus shows increased 18 F-FDG uptake resulting from the increased glycolytic rate in malignant cells. Nevertheless, there are a few cases in the literature with acute venous thrombosis or thrombophlebitis that may cause pathological uptake of 18F-FDG PET [2,3,[6][7][8], although these cases usually demonstrate only "modest 18 F-FDG PET uptake" [9].…”
Section: Discussionmentioning
confidence: 99%
“…Radiolabeled 18 F‐Sodium Fluoride (Na 18 F) was then prepared from the acquired 18 F in‐house as described in the literature 9, 10. Briefly, the process began with 18 F‐fluoride and 0.1 ml H 18 O diluted with 5 ml sterile water and passed through a cation exchange (in the form of H + ) cartridge connected to a Waters Corporation Sep‐Pak Accell Plus QMA cartridge (Milford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%